A preliminary study of EFL reading android application development - Fadel Muslaini; Diah Kristina; Ngadiso Ngadiso (Informascope, 2019)
The present study reports the results of an exploration stage of research and development (RND) whose project is to develop an EFL reading android application. At this exploration stage, this study aims at finding out the possible weaknesses of the existing EFL reading media (textbook) and the needs for an ideal EFL reading android application. 33 tenth grade senior high school students at one of the schools in central Java, Indonesia, were engaged as the participants. Both quantitative questionnaire and qualitative interview to 6 students were assigned to garner the data. This exploration revealed that some weaknesses of the textbook were comprised of monotonous colors, minimum portability, less automatic concept, limited materials, less readable instructions, limited exercises, less direct feedback of the exercises, and insufficient explanations related to EFL reading skill indicators. In turn, the needs analysis data indicated that an EFL reading android application was required to be developed. The developed product was expected to be simple and easily used, motivating and facilitating, up-to-date, providing various EFL reading activities, portable to be used inside and outside of the classroom, and controlling. The ongoing product in the form of the prototype is also presented at the end of this study report.